The Communication Level between the Czech and German Part of the Egrensis Euroregion (Czech Journal of International Relations, 1994)
Research into the intensity of social contacts between municipalities, carried out in the form of a written questionnaire survey, which was part of a joint project, testifies to the current level of contacts between Northern Bavaria and Western Bohemia.' An analysis of the relations between Northern Bavaria and Western Bohemia, in the implementation of which the Pohraničí team also took part (until April 1993 within the Socioeconomic Institute of the Academy of Sciences of the Czech Republic and now as part of the Institute of Sociology of the Academy of Sciences of the Czech Republic). The goal of the investigation was to find out the content and focus of mutual contacts at the level of municipalities and to identify the decisive moments of cross-border cooperation. The content and form of current and planned cross-border contacts, cooperation partners, evaluation of expected and achieved results were examined in detail, especially in connection with the consequences of the opening of borders and the creation of the Egrensis Euroregion. The target group of the written questionnaire survey was heads of district offices, mayors and mayors (possibly Landrate, OberbUrgermeister, BUrgermeister on the German side).Due to the fact that the return from the total number of 417 questionnaires sent out (234 from northern Bavaria and 183 from western Bohemia) represented 61% from the German side and 25% from the Czech side, the result is accordingly shifted in favor of the Bavarian respondents. However, the obtained results - however limited they may be - indicate - the intensity of cross-border cooperation in a given region.